NURTURING HIGH EXPECTATIONS: LIVING A WELL-LIVED CURRICULUM ON A HUMANISTIC PERSPECTIVE - Markus Budiraharjo (Universitas Katolik Indonesia Atma Jaya, 2013)
This study reports an empirical investigation of the use of personalapproach to integrating educational values in an English preserviceteacher education program. Using a Moodle-basedLearning Management System called Exelsa, which has beeen inuse in the past four years, each individual student receivedpersonal written responses from the instructor. Learning isperceived more as a journey to develop self-knowledge that is notmerely driven by instrumental orientations such as grade-seekingmentality, rote memorization, and formalist-driven contents. A setof anedoctal evidence suggested that highly personal notesaddressed to each individual student brought significant change inthe way each of them viewed himself or herself in positive ways.When students felt highly appreciated as significant human beingsin the class, they were more likely to undergo learning more in aholistic manner. A humanistic philosophy of educationnecessitates such an approach to maintaining a relational trustamong all class members. An instructor is supposedly skillful atnavigating the flows of class interactions, at times withunprecedented challenges. A restropective study, this seeks todevelop a better understanding as to whether such an approachleaves a durable significance in their perspectives on learning.Keywords: Humanistic curriculum, high expectation, pre-servicetraining.